1992
DOI: 10.1007/bf01629433
|View full text |Cite
|
Sign up to set email alerts
|

Expression ofHer2/neu oncogene product p185 in correlation to clinicopathological and prognostic factors of gastric carcinoma

Abstract: The expression of the Her2/neu gene product p185 was retrospectively analyzed in 58 patients with gastric carcinoma. The results were correlated to various clinicopathological and prognostic factors. Positive membrane staining for p185 could be detected in 38% of the patients (22/58). Membrane staining was significantly greater in well and moderately differentiated tumors of the intestinal type when compared with poorly differentiated lesions and carcinomas of the diffuse type (P less than 0.01). Positive memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 23 publications
1
36
1
3
Order By: Relevance
“…Our top-ranked gene, ERBB2, is amplified and overexpressed in many cancers, including breast (31), ovary (31), colon (32), bladder (33), non-small-cell lung (34), and gastric cancer (35), and is a poor prognostic factor in certain cancer types (36,37). Several HER2 inhibitors, either tyrosine kinase inhibitors or monoclonal antibodies, are already in clinical use and are invaluable drugs in the treatment of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our top-ranked gene, ERBB2, is amplified and overexpressed in many cancers, including breast (31), ovary (31), colon (32), bladder (33), non-small-cell lung (34), and gastric cancer (35), and is a poor prognostic factor in certain cancer types (36,37). Several HER2 inhibitors, either tyrosine kinase inhibitors or monoclonal antibodies, are already in clinical use and are invaluable drugs in the treatment of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…HER2, which is one of a family of trans-membrane-type epidermal growth factor receptors, is over-expressed in many human malignant neoplasms, such as breast, 23) ovary, 24) endometrium, 25) lung, 26) stomach, 27) colon, 28) esophagus, 29) bladder 30) and pancreas. 31) Also HER2 protein over-expression was reported as a prognostic factor in patients with breast, 8) endometrium, 9) urinary bladder, 11) pancreas 13) and non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of HER2 contributes to the pathogenesis of many cancers including breast, ovarian, gastric, and salivary gland cancers [111][112][113][114]. Stephens et al reported mutations in ERBB2 kinase domain in 4% of the tumor samples from patients with lung cancer [115].…”
Section: Erbb2mentioning
confidence: 99%